Identifikasi dan Karakteristik Kebutuhan Transportasi Perkotaan Kraksaan di Kabupaten Probolinggo - Rifky Aldila Primasworo; M. Sadillah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
Urban public transport describes part of the urban transportation system that plays a very significant role in supporting public mobility. This role makes urban public transportation a very strategic aspect and is expected to be able to accommodate all population activities. The Kraksaan Urban Area is the capital of Probolinggo Regency which is the center of regional activities, both the center of government, the center of trade, and various other economic activities. The purpose of this study is to determine the trip generation and trip attraction (passengers) of the need for urban public transportation, identify route network plans for urban public transportation, identify potential locations for supporting urban public transportation facilities, and direction on the operational performance of urban public transportation. The approach taken is a planning approach, a policy approach related to the development of transportation facilities, a regional approach and a growth approach. The data analysis methods used are passenger characteristics analysis, trip generation and attraction analysis, trip distribution analysis, analysis of public transport operational performance, evaluation of public transport services and SWOT analysis. The result of this research is the characteristics of 71% of the people stating their willingness to change modes and the remaining 29% are not willing. The largest attraction for movement based on the number of facilities is in Patokan, Kraksaan Wetan and Semampir Villages. The external zone of the community comes from outside the Kraksaan District, namely Dringu, Pajarakan, Tegal Siwalan, Gending and Banyuanyar Districts. Zone division based on the planned urban public transportation route in the Kraksaan District Urban Area is divided into two zones, namely the northern and southern zones. Based on the SWOT results, the identification of internal and external factors that affect the performance of public transportation in Urban Kraksaan is obtained.